2018
DOI: 10.1002/hyp.11494
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CFCs and stable isotopes to characterize the mechanism of groundwater–surface water interactions in a headwater basin of the North China Plain

Abstract: Mountainous areas are characterized by steep slopes and rocky landforms, with hydrological conditions varying rapidly from upstream to downstream, creating variable interactions between groundwater and surface water. In this study, mechanisms of groundwater-surface water interactions within a headwater catchment of the North China Plain were assessed along the stream length and during different seasons, using hydrochemical and stable isotope data, and groundwater residence times estimated using chlorofluorocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…For example, some studies reported that topographic characteristics were the main factor influencing F yw , including topographic gradient, elevation and drainage density (Jasechko et al, 2016(Jasechko et al, , 2017Clow et al, 2018). Other studies suggested precipitation, rainfall intensity and groundwater levels were important factors (von Freyberg et al, 2017;Wilusz et al, 2017;Wang et al, 2018). In contrast, a study across 22 contrasting catchments in Germany found no significant correlations between F yw and catchment characteristics (Lutz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies reported that topographic characteristics were the main factor influencing F yw , including topographic gradient, elevation and drainage density (Jasechko et al, 2016(Jasechko et al, , 2017Clow et al, 2018). Other studies suggested precipitation, rainfall intensity and groundwater levels were important factors (von Freyberg et al, 2017;Wilusz et al, 2017;Wang et al, 2018). In contrast, a study across 22 contrasting catchments in Germany found no significant correlations between F yw and catchment characteristics (Lutz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the third-year spin-up from the PF-CLM model were repeatedly used to spin-up the EcoSLIM model for a further 42 years at an hourly time step. We used the results of Wang et al (2018), who sampled groundwater from wells at depths between 2 and 90 m in the mountainous area in our modeling domain and got apparent groundwater ages of these samples from 24 to 42.5 years based on CFC-12 and 25.5-42 years based on CFC-113. Using this field information to guide our model analysis, we stopped the EcoSLIM spin-up at the end of the 42nd year.…”
Section: Numerical Models and Simulationsmentioning
confidence: 99%
“…The majority of the precipitation (75%) falls from June to September (Figure 2). The mean annual air temperature is 13.8 • C and the mean absolute humidity is 61% based on data obtained from the Baoding meteorological station of the China meteorological data-sharing service [14,42]. Location of the study area in Lake Baiyangdian (BYD) watershed (a) and sampling sites in six sections from the Fu River to the Lake BYD watershed (b).…”
Section: Site Descriptionmentioning
confidence: 99%